The efficacy EMDR therapy (Eye Movement Desensitization and Reprocessing) in posttraumatic stress disorder. - Verbenko, Георгій; Myronets, Сергій (Psychosomatic Medicine and General Practice, 2025)
"Eye Movement Desensitization and Reprocessing" (EMDR - Eye Movement Desensitization and Reprocessing) is a psychotherapy method developed by F. Shapiro for the treatment of post-traumatic stress disorders (PTSD) caused by experiencing stressful events, such as violence or participation in military operations. The article provides a comprehensive analysis of the current state of research on the effectiveness of EMDR - therapy for PTSD. Researched scientific works in databases of biomedical literature, including PubMed, Cochrane, Web of Science and Google Scholar. Studies that had meta-analyses of randomized controlled clinical trials of psychotherapeutic methods of PTSD treatment were selected, separately and in comparison with each other and pharmacotherapy. It has been proven that EMDR therapy methods can be used in individual and group format with different population groups. For example, a systematic review (2022) demonstrated the effectiveness of EMDR therapy and its effect on PTSD symptoms, as well as on accompanying anxiety and depression in forcibly displaced people due to natural disasters or social factors (a situation of violence, military actions, persecution). EMDR therapy is a promising, evidence-based therapy that combines clinical and scientific aspects of psychotherapy. It can be used to treat a wide range of disorders, due to the dysfunctional memories were present in clients with all types of clinical diagnoses. Manifestations of inadequately processed memories are dysfunctional patterns of behavior, affective reactions, bodily sensations (psychosomatic and physical symptoms), since long-term memory had the emotional coloring and combines images, thoughts, emotions, and sensations in the body associated with negative experiences. Scientific studies have identified potential neurobiological mechanisms of action for EMDR, which include working memory mechanisms, interhemispheric communication, arousal, and memory reconsolidation. Comparative studies have demonstrated that EMDR therapy may be more effective than CBT in reducing the severity of intrusion and arousal symptoms, while reducing avoidance symptoms of PTSD were about the same. EMDR can be used in group psychotherapy. Additional researches are needed to determine the neurobiological basis of “eye movements” and the interactive effects of the various components EMDR therapy. EMDR refers to short-term therapy, which is of great importance in the treatment of not only an acute stress reaction, but also when conducting therapy for large number of patients. Evidence-based neurobiological studies of the effectiveness of EMDR and the possibility of its use in other mental disorders remain relevant. Key words: psychotherapy, psychological interventions, PTSD, EMDR, neurobiological studies, desensitization